2005
DOI: 10.1021/ma050348k
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Amplified Isomerization:  A New Concept for Polymeric Optical Materials

Abstract: The preparation and evaluation of a new class of photoresponsive polymers are described on the basis of a process called quantum amplified isomerization (QAI). The QAI process utilizes photoinitiated, cation radical isomerization chemistry in a polymeric medium. Two classes of materials are described: one where the QAI reactant is molecularly doped in the polymer matrix and another where the reactant is part of a functionalized polymer. Quantum yield experiments demonstrate that the isomerization reaction can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Lett. 1993, 209, 397. n ) k ET /k IC ≈ 4-8 (6) sion. It was confirmed that, at 60°C, the cyclopropenone moiety is stable and does not thermally decarbonylate.…”
Section: Methodsmentioning
confidence: 97%
“…Lett. 1993, 209, 397. n ) k ET /k IC ≈ 4-8 (6) sion. It was confirmed that, at 60°C, the cyclopropenone moiety is stable and does not thermally decarbonylate.…”
Section: Methodsmentioning
confidence: 97%
“…For example, whereas the carbonyl ylide from epoxide 6 (Scheme 2a) could be trapped with modest efficiency with dimethyl fumarate ( 8 ), epoxide 7 would remain unreacted, only providing trace amounts of the desired product 10 . We have since been able to identify 2,6-di- tert -butylanthracene-9,10-dicarbonitrile (DTAC, 12 ) ( λ max = 431 nm, [DTAC*/DTAC˙ – ] = +1.81 V vs. SCE), a heretofore unknown catalyst in photoredox methodologies, which can selectively generate carbonyl ylides from electron-rich epoxides 12,13. When using DTAC as the catalyst for the cycloaddition of epoxide 6 or 7 with dipolarophile 8 the reaction proceeded in nearly quantitative yields (93–94%) with modest selectivity in both cases for the exo , exo conformer.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the LW is sufficiently more reducible that, even accounting for its lower excitation energy, the LW excited state, LW*, is more reducible than SW*, making LW the more potent photooxidant of the two. However, for practical use as photooxidants, the difference in the reduction potential between LW and SW would need to be increased further, and LW would need to be more reducible to be of use in photooxidation of relevant substrates (e.g., Dewar benzenes, quadricyclanes, or bishomocubanes as quantum amplified isomerization substrates [1115], or vinylcarbazole or alkoxystyrene derivatives for radical cation cylcloaddition and polymerization reactions [1620]). We thus proposed the replacement of the naphthalene in 1a with a more electron-deficient quinoline ring.…”
Section: Introductionmentioning
confidence: 99%